Agrarian Dispute Resolution Institution as a Manifestation of Progressive Legal Transformation - Pratama Maulu, Sigit; M Wantu, Fence; Abdussamad, Zamroni (Cv. Kalimasada Group, 2025)
Indonesia continues to face an increasing number of agrarian conflicts that are complex, multidimensional, and rooted in structural inequality in land control and use. The current litigation-based mechanisms, both in the General Court and the State Administrative Court, are often unable to provide quick, fair, and inclusive resolutions due to procedural rigidity, high costs, and public distrust. Nonlitigation efforts led by government agencies such as the National Land Agency (BPN) also tend to be ineffective due to a lack of neutrality and professional mediation capacity. In response, this study proposes the urgent establishment of an Alternative Dispute Resolution Institution (LAPS) specifically for agrarian disputes. LAPS aims to institutionalize mechanisms such as mediation, negotiation, and conciliation within a professional, independent, and participatory framework. Using a normative juridical method with statutory and conceptual approaches, this research argues that LAPS not only enhances legal certainty and access to justice but also aligns with progressive legal theories, distributive justice, and the sociolegal needs of marginalized communities. The institutionalization of ADR in agrarian law is a transformative step to achieve substantive justice and long-term social stability in land governance in Indonesia. This study found that the current litigation and non-litigation mechanisms are not yet effective in resolving agrarian conflicts fairly and inclusively. Therefore, the establishment of an independent and participatory Agrarian Dispute Resolution Alternative Institution (LAPS) is needed to realize substantive justice and legal certainty in land governance in Indonesia.